Preclinical Pulmonary Capillary Endothelial Dysfunction is Present in Brain Dead Subjects. (1st April 2013) - Glynos, Constantinos; Athanasiou, Chariclea; Kotanidou, Anastasia; Korovesi, Ioanna; Kaziani, Katerina; Livaditi, Olga; Dimopoulou, Ioanna; Maniatis, Nikolaos A.; Tsangaris, Iraklis; Roussos, Charis; Armaganidis, Apostolos; Orfanos, Stylianos E.
Abstract : Pulmonary endothelium is a major metabolic organ affecting pulmonary and systemic vascular homeostasis. Brain death (BD)‐induced physiologic and metabolic derangements in donors' lungs, in the absence of overt lung pathology, may cause pulmonary dysfunction and compromise post‐transplant graft function. To explore the impact of BD on pulmonary endothelium, we estimated pulmonary capillary endothelium‐bound (PCEB)‐angiotensin converting enzyme (ACE) activity, a direct and quantifiable index of pulmonary endothelial function, in eight brain‐dead patients and ten brain‐injured mechanically ventilated controls. No subject suffered from acute lung injury or any other overt lung pathology. Applying indicator‐dilution type techniques, we measured single‐pass transpulmonary percent metabolism (%M) and hydrolysis (v) of the synthetic, biologically inactive, and highly specific for ACE substrate 3 H‐benzoyl‐Phe‐Ala‐Pro, under first order reaction conditions, and calculated lung functional capillary surface area (FCSA). Substrate %M (35 ± 6.8%) and v (0.49 ± 0.13) in BD patients were decreased as compared to controls (55.9 ± 4.9, P = 0.033 and 0.9 ± 0.15, P = 0.033, respectively), denoting decreased pulmonary endothelial enzyme activity at the capillary level; FCSA, a reflection of endothelial enzyme activity per vascular bed, was also decreased (BD patients: 1, 563 ± 562 mL/min vs 4, 235 ± 559 in controls; P = 0.003). We conclude that BD is associated with subtle pulmonary endothelial injury, expressed by decreased PCEB‐ACE activity. The applied indicator‐dilution type technique provides direct and quantifiable indices of pulmonary endothelial function at the bedside that may reveal the existence of preclinical lung pathology in potential lung donors.